Manusia Dalam Islam: Antara Akal, Ruh dan Nafsu - Rica Khairunisa; M.Rizki Mayollie; Carenina Br.Siagian; Dzaky Fadhlu Rahman; Fitria Mayasari; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the role of reason, spirit and passion in human life according to Islamic teachings, and how these three elements interact with each other to achieve a balanced life. The purpose of this research is to understand how Islam teaches the management of reason, spirit and passion as fundamental elements in human life, so that true happiness in this world and the hereafter can be achieved. The method used in this research is literature review and text analysis of the main sources of Islam, such as the Qur'an and Hadith, as well as the opinions of relevant scholars and experts. The results of this study show that Islam emphasizes the importance of maintaining harmony between reason, spirit, and lust through worship, introspection, and self-control. The intellect functions as a tool for wise thinking and decision-making, helping humans understand religious teachings and controlling passions. The spirit as the spiritual essence connects humans with God, providing the impetus to do good and achieve spiritual happiness. Meanwhile, lust, which includes worldly urges, must be controlled so as not to lead humans to pleasures that violate sharia. The study concludes that the balance between these three elements leads to a meaningful life that is in line with the purpose of creation as servants of Allah.